Sistem Pendukung Keputusan Penentuan Handphone Bekas Terbaik Menggunakan Metode Multi-Objective Optimization on The Basis of Ratio Analysis (MOORA) - Ade Septi Rezeki Anggreani Binjori; Hotni Rotua Br Hutapea; Muhammad Syahrizal (JURIKOM (Jurnal Riset Komputer), 2018)
Mobile became one of the important needs for communication today. The development of mobile phone specifications very quickly affect the level of purchases and sales, not only on new phones but also on used mobile phones. The decision to buy used mobile phones requires consideration. This study aims to examine the decision support system for determining the best used mobile phone using Multi-Objective Optimization Method on the Basis of Ratio Analysis (MOORA). The results of this study indicate that MOORA can be used to determine the weight value of each attribute, the ranking process that will select the best mobile alternative from a number of alternatives. Decision Support System makes the process of determining the quality of used mobile phone more efficient than the manual system.